Pengaruh Metode Bercerita terhadap Perkembangan Bahasa Anak Usia 4-5 Tahun di BA Aisyiyah Baleharjo - Apriana; Anantyasari, Malta (IKIP Siliwangi, 2025)
Language development is an important aspect in early childhood education, because it plays a role in communication and literacy. Storytelling methods are often used to improve children's language skills, but their effectiveness still needs further research. This study aims to analyze the effect of storytelling methods on the language development of children aged 4-5 years at BA Aisyiyah Baleharjo. This study used a quantitative approach with a quasi-experimental design, involving 30 children who were divided into experimental and control groups. Data were collected through observation and language tests before and after the intervention, then analyzed using the t-test. The results showed that the storytelling method had a significant effect on pronunciation, understanding of meaning, sentence structure, and children's confidence in communicating. These findings support language acquisition theories, such as Vygotsky's social interaction and Bruner's cognitive processing. This study recommends the application of storytelling methods in early childhood learning and the involvement of teachers and parents to optimize children's language development.